Analisis Pelayanan Aksesibilitas bagi Penyandang Disabilitas di Area Terminal Bandar Udara Tjilik Riwut Palangkaraya - Indriani Indriani; Amelia Puspa Tamara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to identify and analyze the availability and suitability of accessibility facilities, assistance service processes, and service improvement strategies for people with disabilities at Tjilik Riwut Airport in Palangkaraya. The research method employed is a qualitative approach using a descriptive research design. Data collection techniques included observation, interviews, and documentation, with informants consisting of airport staff and parties involved in passenger services. The results indicate that accessibility facilities such as wheelchairs, elevators, accessible restrooms, and access pathways are available; however, they do not yet fully meet accessibility principles, which include ease of use, safety, comfort, and independence. The process of providing assistance to people with disabilities has been carried out through staff accompaniment and a reasonably good service response, although there are still challenges regarding the number of staff, their competence, and coordination among work units. The strategies for service improvement implemented include facility management, maintenance, human resource development, and service evaluation; however, their implementation still needs to be enhanced to achieve optimal results. The conclusion of this study is that accessibility services at Tjilik Riwut Airport in Palangkaraya have been functioning fairly well, but are not yet fully optimized to meet the needs of people with disabilities. Therefore, improvements are needed in terms of facilities, services, and management to achieve more inclusive and sustainable services.